1997
DOI: 10.1093/ije/26.6.1346
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human immunodeficiency virus infection on mortality among young men and women in Spain

Abstract: A, Llácer A, Belza M J, Ruiz C, Pérez de la Paz J and Noguer I. Impact of human immunodeficiency virus infection on mortality among young men and women in Spain. International Journal of Epidemiology 1997; 26: 1346-1351. Background. This paper describes the impact of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) mortality among young adults in Spain with specific reference to other causes of death. Methods. Based on death registration data for the period 1980-1993, HIV/AIDS was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Moreover, AIDS was the main cause of death among young adults during the 1990s26 and drug overdose the second,27 and these causes of death present high socioeconomic inequalities 28 29…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AIDS was the main cause of death among young adults during the 1990s26 and drug overdose the second,27 and these causes of death present high socioeconomic inequalities 28 29…”
Section: Discussionmentioning
confidence: 99%
“…24 25 HIV/AIDS has also been, until recently, the leading cause of death among young adults. 26 GEMES, Spanish Multicentre Study Group of Seroconverters, has consistently reported slower HIV progression rates in women before and after HAART, 20 27 although no differences in the population effectiveness of HAART by gender have been shown. 20 Nevertheless, the heterogeneity of transmission categories within GEMES and the low number of women who are not IDU may hamper the comparisons.…”
mentioning
confidence: 99%
“…Además, esta última sigue constituyendo un problema importante en España, no solo por sus relaciones patogénicas con el sida, sino porque la presencia de infección por VIH acelera la progresión de la TBC, al mismo tiempo que la TBC aumenta la replicación del VIH (30)(31)(32)(33). El sida ha tenido un gran impacto sobre la mortalidad prematura en las dos últimas décadas en España, sobre todo a partir de 1985, dado que es una enfermedad de grupos etarios jóvenes y con una alta letalidad (34,35).…”
Section: Discussionunclassified